Electrolyte and lithium ion battery
By using thermally stable diluents and low viscosity cosolvents in the electrolyte of lithium-ion batteries, the composition of the electrolyte is adjusted, and the contradiction between the fast charging performance and thermal safety performance of lithium-ion batteries is solved, and high fast charging is achieved Comparison of capability and good thermal safety performance.
Patent Information
- Application Number
- CN202411644071.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The fast charging lysate of existing lithium-ion batteries improves fast charging performance while poor thermal safety performance, making it difficult to operate stably in high temperature environments.
By using thermally stable diluents and low viscosity cosolvents in the electrolyte, the composition of the electrolyte is adjusted to improve the diffusion and transport capabilities of lithium ions, while enhancing the thermal safety performance of the electrolyte.
It realizes the high fast charging capability and good thermal safety performance of lithium-ion batteries to ensure that the battery can still operate stably under high temperature environments.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrolytes, in particular to an electrolyte and a lithium ion battery. Background Art
[0002] Lithium-ion batteries have the advantages of high specific energy, high battery voltage, wide operating temperature range and long storage life. They have become one of the most popular charging technologies and are widely used in electric vehicles, aerospace and portable devices.
[0003] With the continuous expansion of application scenarios, lithium-ion batteries are not only required to work normally under normal temperature and high temperature environments, but also need to have good fast charging capabilities, which requires an electrolyte with good fast charging capabilities. In order to improve the fast charging capability of the battery, the electrolyte needs to maintain high ionic conductivity and low interfacial impedance, so low-viscosity linear carbonate solvents are usually added, and additives are minimized or avoided to avoid using high-impedance positive and negative electrode film-forming additives to avoid increasing the impedance of lithium transmission at the electrode / electrolyte interface. However, such a fast-charging electrolyte will have the problem of poor thermal safety performance. Summary of the invention
[0004] In view of the above problems, the present invention provides an electrolyte and a lithium-ion battery. By adding a suitable low-viscosity co-solvent to the electrolyte in a solvent system using a thermally stable diluent, the fast charging performance of the lithium-ion battery can be improved while taking into account its thermal safety performance.
[0005] One aspect of the present invention provides an electrolyte, comprising an organic solvent, a lithium salt, a diluent and a cosolvent. The organic solvent comprises a carbonate solvent, and the mass fraction of the carbonate solvent in the electrolyte is w1, 30%≤w1≤65%; the lithium salt is dissolved in the organic solvent; the diluent does not participate in the solvation reaction of lithium ions in the organic solvent and has flame retardancy, and the mass fraction of the diluent in the electrolyte is w2, 15%≤w2≤50%; the cosolvent is an aromatic compound, and its polarity is between the diluent and the organic solvent, and the mass fraction of the cosolvent in the electrolyte is w3, 5%≤w3≤30%.
[0006] Optionally, the mass ratio of the co-solvent to the diluent is n, n=w3 / w2, and n satisfies the following relationship: 1 / 4≤n≤2.
[0007] Optionally, the diluent is a C3-C8 perfluorinated or polyfluorinated ether diluent.
[0008] Optionally, the diluent is any one of ethyl nonafluorobutyl ether, perfluorobutyl methyl ether, and perfluorobutyl ethyl ether, or a combination of at least two of them; the co-solvent is any one of o-difluorobenzene, m-difluorobenzene, p-difluorobenzene, 1,3,5-trifluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, toluene, ethylbenzene, and trifluoromethylbenzene, or a combination of at least two of them.
[0009] Optionally, the carbonate solvent consists of a cyclic carbonate solvent and a linear carbonate solvent, and the mass fraction of the cyclic carbonate solvent in the carbonate solvent is 5%-20%.
[0010] Optionally, the cyclic carbonate solvent is ethylene carbonate and / or propylene carbonate.
[0011] Optionally, the lithium salt includes any one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, and lithium hexafluoroarsenate, or a combination of at least two thereof, and the mass fraction of the lithium salt in the electrolyte is 10%-20%.
[0012] Optionally, the electrolyte includes additives, the additives include cyclic carbonate additives and lithium salt additives, wherein the cyclic carbonate additive includes any one of vinylene carbonate, fluoroethylene carbonate, and vinyl ethylene carbonate, or a combination of at least two of them; the lithium salt additive includes any one of lithium difluorophosphate, lithium dioxalatoborate, lithium tetrafluoroborate, lithium difluorooxalatoborate, and lithium difluorooxalatophosphate, or a combination of at least two of them; and the mass fraction of the additive in the electrolyte is 0.2%-5.5%.
[0013] Optionally, the lithium salt additive is one or both of lithium difluorooxalatoborate and lithium difluorooxalatophosphate, and the mass fraction of lithium difluorooxalatoborate and / or lithium difluorooxalatophosphate in the electrolyte is 0.1%-0.8%.
[0014] Optionally, the electrolyte includes an additive, and the additive includes a cyclic carbonate additive and methylene disulfonate. The cyclic carbonate additive includes any one of vinylene carbonate, fluoroethylene carbonate, and vinyl ethylene carbonate, or a combination of at least two thereof, and the mass fraction of methylene disulfonate in the electrolyte is 0.1%-0.8%.
[0015] Another aspect of the present invention provides a lithium-ion battery, which includes a positive electrode sheet, a negative electrode sheet and the above-mentioned electrolyte.
[0016] Optionally, the positive electrode plate includes a positive electrode current collector and a positive electrode active material, wherein the positive electrode active material includes any one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide, or a combination of at least two thereof.
[0017] Optionally, the negative electrode plate includes a negative electrode current collector and a negative electrode active material, wherein the negative electrode active material includes any one of soft carbon, hard carbon, artificial graphite, natural graphite, silicon, silicon oxides, silicon carbon compounds, and lithium titanate, or a combination of at least two thereof.
[0018] The fast-charging electrolyte provided in some examples of the present invention uses a low-viscosity diluent substituted with polyfluorine or perfluorine, and reduces the amount of high-melting-point, high-viscosity cyclic carbonate solvents in the organic solvent of the electrolyte, so that the electrolyte forms a local high-concentration system. While ensuring the performance of the electrolyte, the viscosity of the electrolyte can be effectively reduced, so that the lithium ions in the electrolyte can be better diffused and transmitted, and the diluent itself has a stable electrochemical window, which effectively improves the stability of the electrolyte on the positive and negative electrode sides.
[0019] The diluent provided in some examples of the present invention will not participate in the solvation reaction of lithium ions in the electrolyte. By adding the above diluent to the electrolyte and reducing the content of the cyclic carbonate solvent with strong binding ability at the same time, the solvation structure of the lithium ions has sites for the diluent with weak interaction to disperse the anion and cation clusters, which can accelerate the diffusion and transmission process of lithium ions in the electrolyte, thereby improving the fast charging ability of the lithium ion battery, ensuring that the battery still has a low impedance and a high capacity retention rate under high rate charging conditions.
[0020] In some examples of the present invention, the diluent can self-extinguish when the battery cell of the lithium-ion battery thermally runs away, so when such a diluent is added to the electrolyte, the violent reaction can be suppressed when the lithium-ion battery thermally runs away, thereby significantly increasing the thermal runaway temperature of the lithium-ion battery, and further significantly improving its thermal safety performance. On the other hand, since a co-solvent with a polarity between the diluent and the organic solvent and a slightly stronger intermolecular force is added to the electrolyte, this type of co-solvent can also assist in dispersing anion and cation clusters to form easily migrated anion and cation pairs, so that the lithium-ion battery has excellent thermal safety stability while still having good fast charging capabilities. DETAILED DESCRIPTION
[0021] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:
[0023] Solid Electrolyte Interface (SEI): During the charging and discharging process of lithium-ion batteries, the electrode material and the electrolyte react at the solid-liquid interface to form a passivation layer covering the surface of the electrode material.
[0024] In this article, when it comes to numerical ranges, unless otherwise specified, the distribution of optional values within the numerical range is considered continuous and includes the two numerical endpoints (i.e., the minimum value and the maximum value) of the numerical range, as well as every value between the two numerical endpoints. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined.
[0025] In the process of creating the present invention, the inventors analyzed and found that in the prior art, linear carbonate solvents have poor chemical and electrochemical stability with some electrode materials and lithium salts (especially lithium hexafluorophosphate) at high temperatures, and further react with the byproducts produced by the components of lithium salts that decompose at high temperatures, resulting in reduction and gas production. The cyclic carbonate solvent components that help the dissociation of lithium salts are easily oxidized on the surface of the positive electrode (especially the high-nickel positive electrode) to produce gases such as carbon dioxide, accelerating the capacity decay of the battery. On the other hand, the addition of too little high-temperature additives in the electrolyte also affects the stability of the solid electrolyte interface membrane in a high temperature environment. The above factors jointly lead to the problem of poor thermal safety performance of fast-charging electrolytes in the prior art.
[0026] The first aspect of the present invention provides an electrolyte, comprising an organic solvent, a diluent, a co-solvent and a lithium salt. In an embodiment of the present invention, a carbonate solvent is selected as the organic solvent of the electrolyte, and the carbonate solvent includes a cyclic carbonate solvent and a linear carbonate solvent, specifically including any one or a combination of at least two of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate and diethyl carbonate, and the mass fraction of the carbonate solvent in the electrolyte is w1, 30%≤w1≤65%.
[0027] The diluent is a type of diluent that can be used in a local high-concentration electrolyte system, specifically a diluent with a certain flame retardancy, which can improve the self-extinguishing property of the lithium-ion battery. Preferably, the diluent is a C3-C8 perfluoro or polyfluoro substituted ether diluent. More preferably, the diluent includes any one of ethyl nonafluorobutyl ether, perfluorobutyl methyl ether, and perfluorobutyl ethyl ether, or a combination of at least two thereof.
[0028] Since this type of diluent has a low polarity and extremely weak intermolecular forces, it will not participate in the solvation reaction of lithium ions in the electrolyte; at the same time, due to the weak intermolecular forces such as hydrogen bonds between the diluent and the lithium ions, the coordination between the lithium ions and the solvent will be weakened, thereby accelerating the desolvation process of the lithium ions. By adding the above diluent to the electrolyte and reducing the content of the cyclic carbonate solvent with strong binding ability at the same time, the solvation structure of the lithium ions has sites for the diluent with weak forces to disperse the anion and cation clusters, which can accelerate the diffusion and transmission process of lithium ions in the electrolyte, thereby improving the fast charging ability of the lithium-ion battery, ensuring that the battery still has a low impedance and a high capacity retention rate under high-rate charging conditions.
[0029] The above-mentioned diluents contain more fluorine elements, and fluorine elements can self-extinguish when the lithium-ion battery cell thermal runaways. Therefore, when such diluents are added to the electrolyte, violent reactions can be suppressed in the thermal runaway test of the lithium-ion battery, thereby significantly increasing the thermal runaway temperature of the lithium-ion battery and significantly improving its thermal safety performance.
[0030] The mass fraction of the diluent in the electrolyte is w2. In some embodiments of the present invention, when the amount of diluent added to the electrolyte is too small, it has a certain effect on optimizing the secondary battery DC impedance (DCR) of the lithium-ion battery, but the self-extinguishing function of the electrolyte is significantly reduced, which leads to a significant decrease in its thermal runaway temperature; if too much diluent is added to the electrolyte, it will seriously cause the DCR to increase, resulting in a decrease in the fast charging ability of the lithium-ion battery. Therefore, by setting the mass fraction w2 of the diluent within the specified range, the fast charging and thermal safety performance of the lithium-ion battery can be taken into account at the same time, so that it can reach a better level. In some embodiments of the present invention, 15% ≤ w2 ≤ 50%, preferably, 20% ≤ w2 ≤ 40%, more preferably, 25% ≤ w2 ≤ 35%.
[0031] Due to the large difference in polarity between the diluent and the organic solvent in some embodiments of the present invention, it is difficult for the two to be stably dispersed in the electrolyte. To solve this problem, in some examples of the present invention, a co-solvent with a polarity between the diluent and the organic solvent is added to the electrolyte, and this type of co-solvent can also assist in dispersing the anion and cation clusters to form anion and cation pairs that are easy to migrate.
[0032] In some embodiments of the present invention, the co-solvent may be selected from aromatic compounds, for example, any one of o-difluorobenzene, m-difluorobenzene, p-difluorobenzene, 1,3,5-trifluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, toluene, ethylbenzene, and trifluoromethylbenzene, or a combination of at least two thereof. Since such co-solvents have medium polarity and low viscosity, they are conducive to the diffusion of lithium ions. Therefore, when such co-solvents are added to the electrolyte containing the above-mentioned diluent, they can assist in the formation of anion-cation pairs that are easy to migrate, thereby increasing the overall kinetic reaction rate of the lithium-ion battery cell.
[0033] The mass fraction of the co-solvent in the electrolyte is w3. In some embodiments of the present invention, when the amount of co-solvent added to the electrolyte is too small, the DCR of the lithium-ion battery will increase, resulting in a weakened fast charging capability; and when too much co-solvent is added, the mass fraction of the diluent in the electrolyte will decrease, thereby reducing the thermal safety performance of the lithium-ion battery. By setting the mass fraction w3 of the co-solvent within the specified range, the fast charging performance and thermal safety performance of the lithium-ion battery can be simultaneously optimized. In some embodiments of the present invention, 5% ≤ w3 ≤ 30%. Preferably, 7% ≤ w3 ≤ 15%; more preferably, 9% ≤ w3 ≤ 12%.
[0034] The mass ratio of the co-solvent to the diluent is set to n, that is, n=w3 / w2. If the lithium-ion battery is to have a strong fast charging performance while taking into account its thermal safety performance, n satisfies the following relationship: 1 / 4≤n≤2. More preferably, 0.27≤n≤ / 0.4, or 0.3≤n≤ / 0.35.
[0035] Carbonate solvents are composed of cyclic carbonate solvents and linear carbonate solvents. Cyclic carbonate solvents have high dielectric constants and high ion conductivity, and can form a stable solid electrolyte interface film (SEI film) on the negative electrode surface, but they have high viscosity and are often used as organic solvents in electrolytes.
[0036] In the embodiment of the present invention, any one of ethylene carbonate and propylene carbonate or a combination of at least two thereof can be selected as the cyclic carbonate solvent, and any one of dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate or a combination of at least two thereof can be selected as the linear carbonate solvent.
[0037] If the proportion of cyclic carbonate solvents in carbonate solvents is too low, the electrolyte will have insufficient dissociation ability for lithium salts, which will increase the DCR of the lithium-ion battery, thereby reducing its fast charging performance; due to the insufficient stability of cyclic organic solvents on the positive electrode surface, if the proportion of cyclic carbonate solvents in carbonate solvents is too high, the cyclic carbonate solvents will decompose and produce gas on the positive electrode surface, destroying the electrode / electrolyte interface, and ultimately causing the thermal safety performance of the lithium-ion battery to be slightly reduced. By comparing the test results of different groups of embodiments and comparative examples, it is shown that if the mass fraction of cyclic carbonate solvents in carbonate solvents is 5%-20%, and the remaining 80%-95% is linear carbonate solvents, the DCR of the electrolyte and the electrode / electrolyte interface can be kept in a relatively stable state, so that the fast charging performance and thermal safety performance of the lithium-ion battery can be guaranteed.
[0038] After the lithium salt in the electrolyte is dissolved in an organic solvent, a large amount of active lithium ions can be released, so that the electrolyte has good conductivity. The lithium salt can be selected with reference to the conventional types in the field. In the current market with high selectivity electrolyte, the lithium salt contained usually has low dissociation energy and high solubility. The low dissociation energy ensures that the electrolyte formed after the lithium salt is dissolved has a high conductivity, thereby achieving high rate performance of the battery. The high solubility ensures that there are enough lithium ions in the electrolyte for transmission; at the same time, the lithium salt should have good stability, so that when the lithium-ion battery works at high voltage and high temperature, the lithium salt will not react with other components; and if the lithium salt has good SEI film-forming performance, it can ensure that the electrolyte will not be continuously consumed in the subsequent cycle process. In an embodiment of the present invention, the lithium salt includes any one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, and lithium hexafluoroarsenate, or a combination of at least two. The mass fraction of the lithium salt in the electrolyte can be selected according to the conventional proportion in the art. In the present invention, the mass fraction of the lithium salt in the electrolyte is 10%-20%.
[0039] In an embodiment of the present invention, in order to further improve the fast charging capability and thermal safety performance of the lithium-ion battery, the electrolyte includes additives, and the additives include cyclic carbonate additives and lithium salt additives. The cyclic carbonate additive can promote the formation of SEI film and effectively prevent further decomposition of the electrolyte, while improving the low-temperature performance of the electrolyte; the lithium salt additive usually has a high electrochemical stability, which can improve the conductivity of the non-aqueous electrolyte solution, not only can improve the low-temperature output characteristics of the lithium-ion battery, but also can inhibit the decomposition of the positive electrode surface that may occur during the high-temperature cycle and prevent the oxidation reaction of the electrolyte solution, thereby improving the output characteristics after high-temperature storage and swelling characteristics. Among them, the cyclic carbonate additive includes any one of vinylene carbonate, fluoroethylene carbonate, and vinyl ethylene carbonate, or a combination of at least two of them, preferably fluoroethylene carbonate; the lithium salt additive includes any one of lithium difluorophosphate, lithium dioxalate borate, lithium tetrafluoroborate, lithium difluorooxalate borate, and lithium difluorooxalate phosphate, or a combination of at least two of them; the mass fraction of the additive in the electrolyte can be set with reference to the conventional proportion of additives in the electrolyte in the art, and is not limited here. In the embodiment of the present invention, the mass fraction of the additive in the electrolyte is 0.2%-5.5%. Preferably, the mass fraction of the cyclic carbonate additive is 4.5%-5.5%, and the mass fraction of the lithium salt additive is 0.1%-0.8%.
[0040] By combining the performance test results of lithium-ion batteries in some embodiments of the present invention, it is found that when a lithium salt additive is added to the electrolyte as a partial additive, the lithium salt additive is preferably one or two of lithium difluorooxalate borate and lithium difluorooxalate phosphate, and the mass fraction of lithium difluorooxalate borate and / or lithium difluorooxalate phosphate in the electrolyte is 0.1%-0.8%, the fast charge cycle capability and thermal runaway stability of the lithium-ion battery will be more significantly improved. This is because lithium difluorooxalate borate and lithium difluorooxalate phosphate can form a high-quality SEI film on the positive electrode side, which can be beneficial to the improvement of the cycle stability and thermal safety performance of lithium-ion batteries.
[0041] In some embodiments of the present invention, the additive in the electrolyte includes a cyclic carbonate additive and methylene disulfonate. Among them, the cyclic carbonate additive includes any one of vinylene carbonate, fluoroethylene carbonate, and vinyl ethylene carbonate, or a combination of at least two. Preferably, the mass fraction of the cyclic carbonate additive is 4.5%-5.5%. The mass fraction of methylene disulfonate in the electrolyte is 0.1%-0.8%, preferably 0.1%-0.3%. The above embodiments show relatively good fast charging cycle performance and thermal safety performance in the performance test of lithium-ion batteries. This is because after adding methylene disulfonate as an additive to the electrolyte, on the one hand, during the formation and charging of the lithium-ion battery, it will first polymerize on the surface of the positive electrode to form a uniform and dense SEI film. The SEI film, as an interface layer, has the characteristics of a solid electrolyte. It is an electronic insulator but an excellent conductor of lithium ions. Lithium ions can be freely embedded and released through the SEI film. On the other hand, the electrolyte containing the above-mentioned diluent will generate an SEI film mainly composed of inorganic components on the negative electrode side, and can inhibit the reaction between the active lithium of the negative electrode and the SEI film and the electrolyte at high temperature, thereby improving the high-temperature storage performance of the lithium-ion battery and maintaining its cycle stability.
[0042] The second aspect of the present invention also provides a lithium-ion battery, which includes a positive electrode sheet, a negative electrode sheet, a separator and the electrolyte in the above embodiment. During the battery charging and discharging process, lithium ions are embedded and extracted back and forth between the positive electrode sheet and the negative electrode sheet, the separator is arranged between the positive electrode sheet and the negative electrode sheet to play a role of isolation, and the electrolyte plays a role of conducting ions between the positive electrode sheet and the negative electrode sheet.
[0043] The positive electrode plate of the lithium ion battery of the embodiment of the present invention includes a positive electrode current collector and a positive electrode active material. The positive electrode current collector is usually made of a material with good electrical conductivity and mechanical strength, such as copper foil, which is not limited here. As a lithium source in a lithium ion battery, the positive electrode active material is required to provide a higher electrode potential for the lithium ion battery, maintain a stable voltage platform, and have higher ionic and electronic conductivity. The positive electrode active material can be selected with reference to conventional types in the art, including any one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide, or a combination of at least two of them. In the lithium ion battery of the present invention, the positive electrode plate is a lithium nickel cobalt manganese oxide positive electrode plate.
[0044] The negative electrode plate of a lithium-ion battery includes a negative electrode current collector and a negative electrode active material. The negative electrode current collector can be made of a material with good conductivity and mechanical strength, such as copper foil, which is not limited here. In the research field of lithium-ion batteries, the negative electrode active material needs to maintain a stable voltage platform and have a relatively stable structure during the charge and discharge reaction. The negative electrode active material can be selected with reference to the conventional types in the field, including any one of soft carbon, hard carbon, artificial graphite, natural graphite, silicon, silicon oxide compounds, silicon carbon compounds, and lithium titanate, or a combination of at least two of them. Those skilled in the art can choose according to actual needs. In the lithium-ion battery of an embodiment of the present invention, the negative electrode plate uses a graphite-silicon composite negative electrode plate.
[0045] The isolation membrane is selected from conventional types in the art, for example, PE or PP porous membrane can be selected as the isolation membrane, the thickness of the isolation membrane is 9 to 18 μm, the air permeability is 180 s / 100 mL to 380 s / 100 mL; the porosity is 30% to 50%.
[0046] The technical scheme of the present invention is described in detail below through specific examples and comparative examples. Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products, or can be prepared by conventional methods in the art, and the instruments used in the examples are all commercially available.
[0047] The electrolyte compositions of different groups of embodiments and comparative examples are specifically referred to Table 1
[0048] Example 1
[0049] In an argon atmosphere glove box with a water content of <10ppm, battery-grade ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 1:1:8 to form an organic solvent. The lithium salt selected in the electrolyte in Table 1 is lithium hexafluorophosphate (LiPF6), and its concentration in the electrolyte is 1 mol / L; the selected diluent is ethyl nonafluorobutyl ether, and its mass fraction w2 in the electrolyte is 30%; the selected cosolvent is trifluoromethylbenzene, and its mass fraction w3 in the electrolyte is 10%; n is 1 / 3; the additive is fluoroethylene carbonate (FEC), and its mass fraction in the electrolyte is 5%. The above components are combined to obtain an electrolyte. In Table 1, the content of each component except the solvent is the weight percentage calculated based on the total weight of the electrolyte. The preparation method of the electrolyte in other embodiments is the same as that of this embodiment, except that the component ratio is specified in the table.
[0050] Example 2
[0051] The difference between this embodiment and embodiment 1 is that perfluorobutyl methyl ether is selected as the diluent in the electrolyte, and the rest is the same as embodiment 1.
[0052] Example 3
[0053] The difference between this embodiment and embodiment 1 is that w2 is 20%, n is 1 / 2, and the rest is the same as embodiment 1.
[0054] Example 4
[0055] The difference between this embodiment and embodiment 1 is that w2 is 15%, n is 2 / 3, and the rest is the same as embodiment 1.
[0056] Example 5
[0057] The difference between this embodiment and embodiment 1 is that w2 is 15%, w3 is 30%, n is 2, and the rest is the same as embodiment 1.
[0058] Example 6
[0059] The difference between this embodiment and embodiment 1 is that w2 is 20%, w3 is 5%, n is 1 / 4, and the rest is the same as embodiment 1.
[0060] Example 7
[0061] The difference between this embodiment and embodiment 1 is that the mass ratio of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) in the organic solvent is 3:1:6, and the rest is consistent with embodiment 1.
[0062] Example 8
[0063] The difference between this embodiment and embodiment 1 is that the mass ratio of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) in the organic solvent is 0.3:1:8.7, and the rest is consistent with embodiment 1.
[0064] Example 9
[0065] The difference between this embodiment and embodiment 1 is that in addition to fluoroethylene carbonate (FEC), methylene disulfonate (MMDS) is additionally added to the additive. Based on the total mass of the electrolyte, the mass fraction of MMDS is 0.2%, and the rest is consistent with embodiment 1.
[0066] Example 10
[0067] The difference between this embodiment and embodiment 1 is that in addition to fluoroethylene carbonate (FEC), MMDS is additionally added to the additive, and the mass fraction of MMDS is 0.5% based on the total mass of the electrolyte. The rest is consistent with embodiment 1.
[0068] Embodiment 11
[0069] The difference between this embodiment and embodiment 1 is that in addition to fluoroethylene carbonate (FEC), lithium difluorooxalatoborate (LiDFOB) is additionally added to the additive. Based on the total mass of the electrolyte, the mass fraction of LiDFOB is 0.5%, and the rest is consistent with embodiment 1.
[0070] Example 12
[0071] The difference between this embodiment and embodiment 1 is that in addition to fluoroethylene carbonate (FEC), lithium difluorooxalophosphate (LiDFOP) is additionally added to the additive, and the mass fraction of LiDFOP is 0.5% based on the total mass of the electrolyte. The rest is consistent with embodiment 1.
[0072] Example 13
[0073] The difference between this embodiment and embodiment 1 is that, in addition to fluoroethylene carbonate (FEC), lithium tetrafluoroborate (LiBF4) is additionally added to the additive, and the mass fraction of LiBF4 is 0.5% based on the total mass of the electrolyte. The rest is consistent with embodiment 1.
[0074] Comparative Example 1
[0075] The difference between this comparative example and Example 1 is that w2 is 60%, n is 1 / 6, and the rest is consistent with Example 1.
[0076] Comparative Example 2
[0077] The difference between this comparative example and Example 1 is that w2 is 10%, n is 1, and the rest is consistent with Example 1.
[0078] Comparative Example 3
[0079] The difference between this comparative example and Example 1 is that no diluent is added to the electrolyte, n>2, and the rest is the same as Example 1.
[0080] Comparative Example 4
[0081] The difference between this comparative example and Example 1 is that w2 is 20%, w3 is 50%, n is 2.5, and the rest is consistent with Example 1.
[0082] Comparative Example 5
[0083] The difference between this comparative example and Example 1 is that w2 is 15%, no co-solvent is added to the electrolyte, and the rest is the same as Example 1.
[0084] Table 1. Electrolyte compositions of different groups of examples and comparative examples
[0085]
[0086]
[0087] The electrolytes of Examples 1 to 13 and Comparative Examples 1 to 5 were respectively used in the preparation of lithium ion batteries.
[0088] In the embodiments of the present invention, the electrochemical device is a lithium ion battery, and the lithium ion battery is a primary lithium ion battery or a secondary lithium ion battery, comprising: a positive electrode sheet, a negative electrode sheet, a separator between the positive electrode and the negative electrode, and an electrolyte. The preparation method of the secondary lithium ion battery in some embodiments of the present invention is as follows:
[0089] (1) Preparation of lithium nickel cobalt manganese oxide positive electrode
[0090] The positive electrode active material (LiNi 0.8 Co 0.1 Mn 0.1 O2), polyvinylidene fluoride as a binder and Super P as a conductive agent are mixed in a weight ratio of 98:1:1, and then N-methylpyrrolidone (NMP) is added to the mixture. The mixed system is stirred by a vacuum mixer until it becomes a uniform and transparent mixed solution to obtain the positive electrode slurry; the positive electrode slurry is evenly coated on the aluminum foil; the aluminum foil is dried at room temperature and then transferred to an oven for drying, and then cold pressed and cut to obtain the positive electrode sheet.
[0091] (2) Preparation of graphite-silicon composite negative electrode sheet:
[0092] A mixture obtained by mixing artificial graphite with a silicon-carbon composite in a mass ratio of 9:1 is used as a negative electrode active material, Super P is used as a conductive agent, sodium carboxymethyl cellulose (CMC-Na) is used as a thickener, and styrene-butadiene rubber (SBR) is used as a binder. The negative electrode active material, conductive agent, thickener, and binder are mixed in a mass ratio of 96:1:1:2, deionized water is added, and the mixed substances are stirred evenly by a vacuum mixer to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on a negative electrode current collector copper foil; the copper foil is then dried at room temperature and then transferred to an oven for drying, and finally cold pressed and cut to obtain a negative electrode sheet.
[0093] (3) Preparation of electrolyte
[0094] In an argon atmosphere glove box with a water content of <10ppm, battery-grade ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) are mixed in the mass ratio shown in Table 1 to form an organic solvent. The lithium salt selected in the electrolyte in Examples 1-13 and Comparative Examples 1-5 of the present invention is lithium hexafluorophosphate, and the lithium salt concentration is 1 mol / L. The types of diluents, cosolvents, and additives and the mass fractions based on the total weight of the electrolyte are all based on the settings of Examples 1-13 and Comparative Examples 1-5 in Table 1 above. The above components are mixed to obtain an electrolyte. In Table 1, the content of each component except the organic solvent is the mass percentage calculated based on the total mass of the electrolyte; the electrolytes in different embodiments and comparative examples are prepared in the same manner except that the component ratios are specified in the table.
[0095] (4) Preparation of isolation membrane
[0096] A 12 μm polypropylene film (PP) was selected as the isolation film.
[0097] (5) Preparation of secondary lithium-ion batteries
[0098] The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked in sequence, with the separator placed between the positive and negative electrode sheets to play a role of isolation. Then, the sheet is wrapped with aluminum plastic film, transferred to a vacuum oven for drying at 120°C, and sealed after injecting 3.0g / Ah of the electrolyte prepared above, and the electrolyte is formed, and finally a soft-pack battery (i.e., lithium-ion battery) with a capacity of 1Ah is prepared.
[0099] The performance of lithium-ion batteries assembled from the electrolytes in Examples 1-13 and Comparative Examples 1-5 was tested. The test results are shown in Table 2. The test method is as follows:
[0100] (1) Secondary lithium-ion battery DC resistance (DCR) test
[0101] At a specified temperature, when the secondary lithium-ion battery is discharged to 50% SOC (state of charge, reflecting the remaining capacity of the battery) at a current of 1C, the current is increased to 4C and maintained for 30s. The difference between the updated stable voltage and the original platform voltage is detected. The ratio of its value to the 4C current value is the DC impedance of the battery. The DCR test result after the battery is fully charged for the first time is the initial DCR of the battery.
[0102] (2) Secondary lithium-ion battery cycle test
[0103] In an oven at a specified temperature (room temperature 25°C or high temperature 45°C), the lithium-ion battery is charged at a current of 3C and discharged at a current of 1C. The charge and discharge are cyclically performed within a specified potential range, and the discharge capacity of each cycle is recorded. The test is terminated when the battery capacity reaches 80% of the first cycle capacity, and the number of battery cycles is recorded.
[0104] (3) Secondary lithium-ion battery hot box test
[0105] The secondary lithium-ion battery was fully charged to 4.25 V and subjected to a hot box test (130° C., 30 min, followed by gradual temperature increase until thermal runaway).
[0106] For lithium nickel cobalt manganese oxygen / silicon-graphite batteries, the charge and discharge cut-off voltage is: 2.5-4.25V.
[0107] Table 2. Performance test results of different groups of lithium-ion batteries of examples and comparative examples
[0108]
[0109] Analyzing the above data, we can draw the following conclusions:
[0110] By comparing Examples 1-2 and Comparative Example 3, it can be seen that adding diluents such as ethyl nonafluorobutyl ether and perfluorobutyl methyl ether to the electrolyte can significantly increase the temperature of thermal runaway. This is because such diluents contain more fluorine elements, which can suppress the violent heat release of the reaction in the thermal runaway test.
[0111] By comparing Examples 1, 3, 4 and Comparative Examples 1-2, it can be seen that when too little diluent is added to the electrolyte, although the DCR is optimized to a certain extent, the thermal runaway temperature of the lithium-ion battery decreases significantly due to the reduced self-extinguishing function of the electrolyte. When too much diluent is added, the DCR will be seriously deteriorated, resulting in a decrease in the fast charging ability of the lithium-ion battery. Therefore, the amount of diluent added should be controlled within the prescribed range to take into account the fast charging and thermal safety performance of the lithium-ion battery. Within the optimal dosage range, increasing the amount of diluent will slightly deteriorate the DCR and fast charging performance of the lithium-ion battery, but will improve its thermal safety performance. This is because such diluents have a large viscosity and no ability to dissociate lithium salts, resulting in a certain degree of reduction in the conductivity of the electrolyte.
[0112] By comparing Examples 1, 4-6 and Comparative Examples 4 and 5, it can be seen that when too little co-solvent is added to the electrolyte containing the diluent, the DCR of the lithium-ion battery will increase significantly and reduce its fast charging ability, because at this time the electrolyte lacks a co-solvent with medium polarity to assist in the formation of anion-cation pairs that are easy to migrate, which makes the overall dynamics of the battery cell worse. When too much co-solvent is added to the electrolyte, the proportion of diluent will decrease, resulting in a deterioration in the thermal safety performance of the lithium-ion battery. Within the optimal dosage range, increasing the amount of co-solvent will slightly improve the DCR and fast charging performance. This is because such co-solvents have low viscosity and can help the diffusion of lithium ions.
[0113] Comparing Examples 1, 7, and 8, it can be seen that if the proportion of cyclic carbonate solvents in carbonate solvents is too low, the electrolyte will have insufficient dissociation ability for lithium salts, thereby causing the DCR of the lithium-ion battery to have a certain deterioration performance. If the proportion of cyclic carbonate solvents in carbonate solvents is too high, the cyclic carbonate organic solvents themselves will decompose and produce gas due to insufficient stability on the positive electrode surface, thereby deteriorating the interface stability between the electrode and the electrolyte, and ultimately slightly reducing the thermal safety performance of the lithium-ion battery. Preferably, the cyclic carbonate solvent, such as ethylene carbonate and / or propylene carbonate, accounts for 5%-20% by mass in the carbonate solvent.
[0114] By comparing Examples 1, 9, and 10, it can be seen that when MMDS is added to the electrolyte as a partial additive, on the one hand, when the lithium-ion battery is formed and charged, the positive electrode surface will first polymerize to form a uniform and dense SEI film, and on the other hand, the electrolyte containing the diluent will generate an SEI film mainly composed of inorganic components on the negative electrode side, and can inhibit the reaction of the negative electrode activity with the SEI film and the electrolyte at high temperature, improve the high temperature storage performance of the lithium-ion battery, and maintain its fast charging cycle stability. Therefore, the fast charging cycle of the lithium-ion battery with the addition of MMDS has good performance, and the interfaces between the positive and negative electrodes and the electrolyte are relatively stable, which can improve the thermal safety performance of the lithium-ion battery to a certain extent.
[0115] Comparing Examples 1, 11-13, it can be seen that LiDFOB and LiDFOP have a more significant improvement on the fast charge cycle capability of lithium-ion batteries and the increase in the runaway temperature of the hot box than LiBF4. This is because the quality of LiDFOB and LiDFOP film formation on the positive electrode side is better than that of LiBF4, which is conducive to the improvement of cycle stability and thermal safety performance, so LiDFOB or LiDFOP is preferred as the lithium salt additive.
[0116] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An electrolyte, characterized in that: include: An organic solvent, wherein the organic solvent comprises a carbonate solvent, and the mass fraction of the carbonate solvent in the electrolyte is w1, 30%≤w1≤65%; A lithium salt dissolved in the organic solvent; A diluent that does not participate in the solvation reaction of lithium ions in the organic solvent and has flame retardancy, wherein the mass fraction of the diluent in the electrolyte is w2, 15%≤w2≤50%; A co-solvent, wherein the co-solvent is an aromatic compound, the polarity of the co-solvent is between the diluent and the organic solvent, and the mass fraction of the co-solvent in the electrolyte is w3, 5%≤w3≤30%.
2. The electrolyte according to claim 1, characterized in that The mass ratio of the co-solvent to the diluent is n, n=w3 / w2, and n satisfies the following relationship: 1 / 4≤n≤2.
3. The electrolyte according to claim 1, characterized in that The diluent is a C3-C8 perfluorinated or polyfluorinated ether diluent.
4. The electrolyte according to claim 1, characterized in that The diluent is any one of ethyl nonafluorobutyl ether, perfluorobutyl methyl ether, and perfluorobutyl ethyl ether, or a combination of at least two thereof; The co-solvent is any one of o-difluorobenzene, m-difluorobenzene, p-difluorobenzene, 1,3,5-trifluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, toluene, ethylbenzene, and trifluoromethylbenzene, or a combination of at least two thereof.
5. The electrolyte according to claim 1, characterized in that The carbonate solvent consists of a cyclic carbonate solvent and a linear carbonate solvent, and the mass fraction of the cyclic carbonate solvent in the carbonate solvent is 5%-20%.
6. The electrolyte according to claim 5, characterized in that The cyclic carbonate solvent is ethylene carbonate and / or propylene carbonate.
7. The electrolyte according to claim 1, characterized in that The lithium salt includes any one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, and lithium hexafluoroarsenate, or a combination of at least two thereof, and the mass fraction of the lithium salt in the electrolyte is 10%-20%.
8. The electrolyte according to claim 1, characterized in that Also included are additives, the additives comprising: A cyclic carbonate additive, wherein the cyclic carbonate additive includes any one of vinylene carbonate, fluoroethylene carbonate, and vinyl ethylene carbonate, or a combination of at least two thereof; and A lithium salt additive, wherein the lithium salt additive includes any one of lithium difluorophosphate, lithium dioxalatoborate, lithium tetrafluoroborate, lithium difluorooxalatoborate, and lithium difluorooxalatophosphate, or a combination of at least two thereof; The mass fraction of the additive in the electrolyte is 0.2%-5.5%.
9. The electrolyte according to claim 8, characterized in that The lithium salt additive is one or both of the lithium difluorooxalatoborate and the lithium difluorooxalatophosphate. The mass fraction of the lithium difluorooxalatoborate and / or the lithium difluorooxalatophosphate in the electrolyte is 0.1%-0.8%.
10. The electrolyte according to claim 1, characterized in that Also included are additives, the additives comprising: A cyclic carbonate additive, wherein the cyclic carbonate additive includes any one of vinylene carbonate, fluoroethylene carbonate, and vinyl ethylene carbonate, or a combination of at least two thereof; and Methylene methane disulfonate, wherein the mass fraction of the methylene methane disulfonate in the electrolyte is 0.1%-0.8%.
11. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet and an electrolyte according to any one of claims 1 to 10.
12. The lithium ion battery according to claim 11, characterized in that The positive electrode sheet comprises: a positive electrode current collector; and The positive electrode active material includes any one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide, or a combination of at least two thereof.
13. The lithium ion battery according to claim 11, characterized in that The negative electrode plate comprises: a negative electrode current collector; and The negative electrode active material includes any one of soft carbon, hard carbon, artificial graphite, natural graphite, silicon, silicon oxide, silicon carbon compound, and lithium titanate, or a combination of at least two thereof.
Citation Information
Patent Citations
Non-aqueous electrolyte, preparation method thereof and application thereof in lithium ion battery
CN111180796A
Thermal desorption-gas chromatography-mass spectrometry detection method for hydrofluoroether solvent in air
CN113156033A
Non-combustible practical carbonic ester-based electrolyte compatible with graphite negative electrode and application of non-combustible practical carbonic ester-based electrolyte
CN116706242A
Local high-concentration electrolyte containing functional additive
CN116826164A
Electrolyte and lithium battery containing same
CN117790893A
Cited By
Lithium secondary battery and electric device
WO2026179405A1